Education and informed consent about increased risk donor kidneys: a national survey of non‐physician transplant providers. Issue 2 (13th March 2014) - Gordon, E.J.; Mullee, J.; Beauvais, N.; Warren, E.; Theodoropoulos, N.; McNatt, G.; Rassiwala, J.; Ison, M.G.
Abstract Introduction Transplant providers must understand the definition of increased risk donor (IRD) organs to effectively educate transplant candidates and obtain informed consent. This study surveyed non‐physician providers from 20 transplant centers about their educational and informed consent practices of IRD kidneys. Methods An anonymous, web‐based survey about the content and timing of education and informed consent for potential recipients of IRD kidneys, providers' knowledge of IRD kidneys, and provider and center characteristics was completed by most (67%; 90 of 135) of those invited to participate; 87 responses were included in analysis. Results Most (80%) reported understanding the concept of IRD kidneys. However, few reported sufficient knowledge of the Organ Procurement and Transplantation Network definition of IRDs, risk factors, screening tests, window periods, and infection transmission rates. Most (56%) felt uncomfortable with obtaining specific informed consent for IRD kidneys. Most respondents received informal education about IRD kidneys (78%), and recognized the need for (98%) and were interested in receiving (99%) further education on this topic. Conclusion Non‐physician transplant providers need and are interested in better education about IRD kidneys to effectively educate patients and obtain patients' informed consent.